Sociología y política, el debate clásico y contemporáneo - Zabludovsky, Gina. (Colección Las Ciencias sociales., 1995)
"Noteworthy contribution reflects on central problems of contemporary and classical theory and attempts to bridge European/US and Mexican thought. Addresses democracy and implications of globalization on social theory. Includes an imaginary dialogue between De Tocqueville and Lorenzo de Zavala, an analysis of challenges to the discipline using Gidden's 'radicalized modernity' concept, and a diagnostic of sociology in Mexico"--Handbook of Latin American Studies, v. 57.